2011
DOI: 10.1189/jlb.0910510
|View full text |Cite
|
Sign up to set email alerts
|

Arginine transport in human monocytic leukemia THP-1 cells during macrophage differentiation

Abstract: L-arginine metabolism in myeloid cells plays a central role in the processes of macrophage activation and in the regulation of immune responses. In this study, we investigated arginine transport activity and the expression of the related transporter genes during the differentiation of monocytes to macrophages. We show here that the induction of THP-1 monocyte differentiation by PMA markedly increases the expression of SLC7A7 mRNA and of y ϩ LAT1 protein and consequently, the activity of system y ϩ L-mediated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
2
29
1
2
Order By: Relevance
“…Toll-like receptor signalling, especially a response to viral DNA, has been shown to be impaired, and nitric oxide (NO) production decreased in LPI monocyte-derived macrophages reinforcing the role of macrophages in the development of secondary complications of LPI (Kurko et al 2015). We hypothesized that, in contrast to the earlier suggestions by other groups (Sebastio et al 2011;Ogier de Baulny et al 2012), arginine reservoirs and the subsequent NO levels may actually be diminished in LPI macrophages as a result of reduced arginine influx by the defective y + LAT1 transporter, known to be the most important transporter of arginine in macrophages, including those of alveolar origin (Barilli et al 2011;Rotoli et al 2007). In addition, the defective CAA transport also results in impaired phagocytic activity of LPI macrophages (Barilli et al 2012).…”
Section: Discussioncontrasting
confidence: 45%
“…Toll-like receptor signalling, especially a response to viral DNA, has been shown to be impaired, and nitric oxide (NO) production decreased in LPI monocyte-derived macrophages reinforcing the role of macrophages in the development of secondary complications of LPI (Kurko et al 2015). We hypothesized that, in contrast to the earlier suggestions by other groups (Sebastio et al 2011;Ogier de Baulny et al 2012), arginine reservoirs and the subsequent NO levels may actually be diminished in LPI macrophages as a result of reduced arginine influx by the defective y + LAT1 transporter, known to be the most important transporter of arginine in macrophages, including those of alveolar origin (Barilli et al 2011;Rotoli et al 2007). In addition, the defective CAA transport also results in impaired phagocytic activity of LPI macrophages (Barilli et al 2012).…”
Section: Discussioncontrasting
confidence: 45%
“…Interestingly, it has been shown that an increase in Slc7a7 expression and Arginine transport is characteristic of human monocyte differentiation into macrophages in vitro. Knocking down Slc7a7 in monocytes leads to Arginine accumulation in these cells (Barilli et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the CAT family of proteins in hematopoiesis has only received limited study, identifying CAT-1 and CAT-2B as the main transporters responsible for arginine uptake in in vitro models of nonmalignant myeloid and erythroid cells. [34][35][36] Arginine can be produced within healthy cells, by the ornithinecitrulline-arginine cycle. 37,38 We identified that the majority of patients' blasts are deficient in either ASS or OTC enzymes, strongly suggesting that AML blasts are reliant on extracellular arginine availability.…”
Section: Discussionmentioning
confidence: 99%